The Relationship Between Self Esteem And Gambling Motivation:A Study Among Casino Customers - Thomson , Albino Roshan (International Journal of Psychosocial Rehabilitation, 2020)
Many studies have shown that persons with low self esteem are vulnerable to different types of addictive behavior. Gambling is such a behavior to which persons can get addicted easily. This paper examines the relationship between self esteem and gambling motivation. Self esteem and gambling motivation scales were administered to 108 casino customers in Goa, India. Factor analysis of self esteem resulted in three dimensions namely negative self-worth, self-worth and other oriented self-worth. Gambling motivation loaded onto five factors namely basic motives, escape motives, achievement motives, enjoyment motives and socialization motives. Further, regression analysis revealed that negative self-worth was significantly positively associated with basic motives, escape motives and socialization motives. The other two dimensions of self esteem were not associated with any of the dimensions of gambling motivation. It is interesting to note that achievement motive and enjoyment motives were not predicted by even negative self-worth. The findings are of theoretical importance as to the relation between negative self-worth and negative types of motivations and practical significance for casinos as well as for addiction counselors.